2018
DOI: 10.1016/j.freeradbiomed.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional changes in RNAse A originating from tyrosine and histidine cross-linking and oxidation induced by singlet oxygen and peroxyl radicals

Abstract: Oxidation can be induced by multiple processes in biological samples, with proteins being important targets due to their high abundance and reactivity. Oxidant reactions with proteins are not comprehensively understood, but it is known that structural and functional changes may be a cause, or a consequence, of disease. The mechanisms of oxidation of the model protein RNAse A by singlet oxygen (O) were examined and compared to peroxyl radical (ROO) oxidation, both common biological oxidants. This protein is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Photosensitizers can produce 1 O 2 under the irradiation of UV or visible light, and many studies have shown that L‐Tyrosine (L‐Tyr) is the main oxidation target of 1 O 2 40–42 . After L‐Tyr is oxidized, the fluorescence intensity at 305 nm will decrease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photosensitizers can produce 1 O 2 under the irradiation of UV or visible light, and many studies have shown that L‐Tyrosine (L‐Tyr) is the main oxidation target of 1 O 2 40–42 . After L‐Tyr is oxidized, the fluorescence intensity at 305 nm will decrease.…”
Section: Methodsmentioning
confidence: 99%
“…Photosensitizers can produce 1 O 2 under the irradiation of UV or visible light, and many studies have shown that L-Tyrosine (L-Tyr) is the main oxidation target of 1 O 2 . [40][41][42] After L-Tyr is oxidized, the fluorescence intensity at 305 nm will decrease. Therefore, the photodynamic activity of photosensitizers can be characterized by measuring the change of the fluorescence intensity of L-Tyr in the sample solution.…”
Section: Photodynamic Activity Of the Mpeg-pba@ppixmentioning
confidence: 99%
“…Di-Tyr crosslinks have also been detected on synthetic peptides exposed to peroxidase activity (e.g., hemoglobin and H 2 O 2 [ 141 ]), and a large number of isolated proteins including (amongst others): lipoproteins [ 61 , 70 , 71 ], glucose 6-phosphate dehydrogenase (G6PDH) [ 53 ], ribonuclease A (RNAse A) [ 86 ], multiple extracellular matrix proteins [ 57 , 58 , 76 ], calmodulin [ 72 ], lysozyme [ 54 , 79 ], myoglobin [ 142 , 143 ], insulin [ 48 , 73 , 74 ] and human Δ25 centrin 2 [ 75 ].…”
Section: Types Of Crosslinks Detected Within and Between Proteins And Peptidesmentioning
confidence: 99%
“…products was determined on peptides generated by tryptic digestion as described previously [31][32][33] . Samples (150 µg protein) were prepared as described above, then subjected to buffer exchange into 100 mM ammonium bicarbonate buffer (ABC buffer) using spin filters (10 kDa cut-off).…”
Section: Mass Spectrometric Analysis Of Oxidation Products the Detecmentioning
confidence: 99%
“…Carbamidomethylation of cysteine was used as a fixed modification. Data was filtered in order to extract peptide-spectrum matches corresponding to established oxidative modifications using a list of known oxidative modifications 36 , with changes at Met, His, Tyr and Pro as variable modifications 29,31 . The % modification at a particular site was estimated using label-free quantification ratios relative to the parent, as determined using Maxquant.…”
Section: Mass Spectrometric Analysis Of Oxidation Products the Detecmentioning
confidence: 99%